Improving profitability and sustainability in dual-purpose and irrigated wheat systems - Bott, Claire (My University, 2026)
Kansas is the top wheat-producing state in the United States, producing around 7.9 Mt of grain annually. Most of this wheat is hard red winter wheat (Triticum aestivum L.), grown in the water limited regions of western and central Kansas. Although rainfed grain-only production systems are dominant, Kansas is home to a diversity of other wheat production systems. This thesis explores two alternative wheat cropping systems - dual-purpose wheat and irrigated wheat - through the lenses of profitability and sustainability. The first study (chapter two) addressed dual-purpose wheat and aimed to assess and optimize timing recommendations for grazing cessation. A thorough literature review revealed that the current recommendation to terminate grazing at 1.5 cm of hollow stem lacks scientific backing. Building on this, nine years of field data from Hutchinson, Kansas, were analyzed to better inform grazing termination recommendations. Each year, dual purpose and grain only management experiments were sown within the same field, along with a third experiment planted with the same management as the dual purpose plots but not defoliated and instead used to monitor crop development. Results showed that the current 1.5 cm recommendation is too late to avoid grain yield penalization, and that grain yield reduction begins at approximately 0.6 cm of hollow stem. Economic analysis further revealed that increases in forage from extended grazing rarely offset monetary losses from reduced grain yield. Chapter three examined irrigated wheat production as a strategy to improve the sustainability of groundwater use in the High Plains Aquifer. Regional-scale, sustainable irrigation targets were developed based on maintaining long-term aquifer water balance (Irr Q-stable), and crop simulations using DSSAT v4.6.1.0 (CERES-Wheat and CERES-Maize) were conducted for continuous maize, continuous wheat, and maize–wheat rotations across 30 years of historical weather in nine regions. Results demonstrated that crop choice is a powerful driver of irrigation sustainability: continuous wheat remained within sustainable irrigation limits across all regions, whereas continuous maize frequently exceeded those limits, indicating that shifts toward wheat or maize–wheat rotations can substantially reduce groundwater pumping without reducing irrigated land area. Survey data from irrigated wheat producers supported these findings, with 85% of fields remaining below sustainable pumping thresholds. Crop modeling further showed that, while most producers already apply irrigation volumes near those required to achieve yield potential, optimizing irrigation timing enabled 77% of surveyed fields to reach within 10% of their simulated yield potential. These findings highlight that improving irrigation scheduling and agronomic management, alongside strategic crop selection, offers a pathway to increase water use efficiency. Together, these chapters provide evidence-based recommendations to improve the profitability of dual-purpose wheat and the long-term sustainability of irrigated wheat production, demonstrating how management and cropping system decisions can simultaneously support producer profitability and conserve groundwater resources in often overlooked Kansas wheat production systems.
Keywords: Wheat; Irrigation; Sustainability; Grazing